CARBOHYDRAT BY DIFFERENT ANALYSIS OF DRAGON FRUIT LEATHER TEA - Rini Fertiasari (Universitas Teuku Umar, 2021)
The key to managing blood sugar levels is managing carbohydrate intake. This is because carbohydrates are responsible for raising blood sugar levels. Managing the quantity of carbohydrates is the main goal, although choosing slow-digesting carbohydrates with high fiber content also helps. Apart from carbohydrates, people with diabetes need to also limit their intake of salt, saturated fat, and avoid trans fats. For people with diabetes, it is highly recommended to include fiber and healthy fats in the daily diet. The research aims to: 1. Know the differences in carbohydrate content consisting of starch, reduced sugar and crude fiber in dragon skin tea mechanically and manually, 2. Knowing the carbohydrate content different; 3. Knowing the number of calories in a 100 gram serving of tea. The treatments were carried out using two drying techniques, namely oven drying (mechanical) and manual drying (sunlight). The test carried out is proximate testing. The resulting product is a functional food processed product that has an additional function as a food processing product for health. The herbal tea is made from red dragon fruit skin as raw material. Red dragon fruit skin tea has a function as a medicine for type 2 diabetes mellitus. From the laboratory test results obtained by different carbohydrate values for dragon skin tea with mechanical treatment is 41.83% and the total calorie is 201.57 kcal per 100 grams.